2006
DOI: 10.1890/1051-0761(2006)016[1619:petcos]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Predators Exert Top-Down Control of Soybean Aphid Across a Gradient of Agricultural Management Systems

Abstract: The discovery of soybean aphid, Aphis glycines Matusumura, in North America in 2000 provided the opportunity to investigate the relative strength of top-down and bottom-up forces in regulating populations of this new invasive herbivore. At the Kellogg Biological Station Long Term Ecological Research site in agroecology, we contrasted A. glycines establishment and population growth under three agricultural production systems that differed markedly in disturbance and fertility regimes. Agricultural treatments co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
145
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(161 citation statements)
references
References 77 publications
12
145
1
Order By: Relevance
“…Previous studies have shown natural enemies to have a large impact on the regulation of soybean aphid populations , Costamagna and Landis 2006, Schmidt et al 2007, Gardiner et al 2009b. In all cases, these studies focused on the growth of initial populations of aphids at low densities (1Ð10 aphids per plant).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown natural enemies to have a large impact on the regulation of soybean aphid populations , Costamagna and Landis 2006, Schmidt et al 2007, Gardiner et al 2009b. In all cases, these studies focused on the growth of initial populations of aphids at low densities (1Ð10 aphids per plant).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the large body of literature that indicates natural enemies regulate soybean aphid populations (Fox et al , 2005Rutledge et al 2004;Nielsen and Hajek 2005;OÕNeil 2005, Costamagna andLandis 2006;Schmidt et al 2007Schmidt et al , 2008, economic outbreaks are common in North America. Why these outbreaks occur is unclear, although several factors can contribute to increasing the risk for soybean aphid outbreaks.…”
mentioning
confidence: 99%
“…The presence of decomposing organic matter at the soil surface, characteristic of no-till systems, provides predators with alternative prey when crop pests are scarce thus maintaining predator populations in fallow periods or in annual cropping systems (Landis, Wratten, and Gurr 2000;Sigsgaard 2000). Yet, some predator groups, such as carabid (Hatten et al 2007) and coccinellid beetles (Costamagna and Landis 2006), demonstrate more idiosyncratic responses. Likewise, some soil practices that increase the area of bare ground and increase loosening of compacted soils (RogerEstrade et al 2010) can have positive effects on ground-nesting bees (Julier and Roulston 2009).…”
Section: Soil Management Practicesmentioning
confidence: 99%
“…Natural enemies are capable of suppressing soybean aphid populations (Fox et al, 2004;Costamagna and Landis, 2006;Desneux et al, 2006;Brosius et al, 2007). The presence of natural enemies influences the withinplant distribution of many aphid species (Roitberg et al, 1979;Gonzales et al, 2001), and potentially soybean aphid (Rutledge and O'Neil, 2005).…”
mentioning
confidence: 99%